Chrześcijanie w łagrze (w wybranych dziełach literatury polskiej i rosyjskiej) - Sucharski, Tadeusz (Slavia Occidentalis, 2016)
The aim of this article is to reflect on the religiosity of Stalinist prisoners shaped by religion or the Christian tradition. A comparison of works of Polish and Russian literature demonstrates that prisoners from the Soviet Union and Poland essentially otherwise referred to the faith, to the Decalogue. Most of the inmates came into the camp from the country’s militant atheism, infected with a hostility to religion as “the opium of the masses”, and only in the camp were they looking for ways to return to the faith of their fathers. However, they often kept faith in the value of humanity, they represented a secular holiness. A substantial majority of Polish prisoners affirmed their Catholicism, which was not only a witness of their faith, but also synonymous with Polish culture. Such an attitude often hampered relations with the Orthodox and Greek Catholics. A large part of the Polish inmates reluctantly referred to them as Christians of the Eastern Rite, as a consequence of Catholic education in pre-war Poland, but also out of hostility towards Russians and Ukrainians. Many of them, however, disregarded religious issues, they referred to a fellow prisoner with respect, regardless of his religion. They looked at them from the human perspective.